2013
DOI: 10.3109/01460862.2013.825989
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric pressure injuries: does modifying a tool alter the risk assessment outcome?

Abstract: The aim of this study was to determine whether assessing patient risk of developing pressure injuries in Pediatric Intensive Care (PICU) and Neonatal Units (NNU) using a modification of the Glamorgan Scale (mGS) would alter the risk identification when compared to the Glamorgan Scale (GS). Prospective data were collected from a convenience sample of patients admitted to PICU or NNU during a 2-month period. The patients' pressure injury risk score using both instruments was collected by observing patients, revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The Glamorgan Scale has been modified (mGS), and even though it is simpler in terms of usability and efficiency, it has been observed that this tool is equally effective in categorizing patients as the original Glamorgan Scale, producing the same categorization of risk in the assessment of pediatric patients 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The Glamorgan Scale has been modified (mGS), and even though it is simpler in terms of usability and efficiency, it has been observed that this tool is equally effective in categorizing patients as the original Glamorgan Scale, producing the same categorization of risk in the assessment of pediatric patients 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies assessed validity and reliability of risk assessment tools, including Waterlow 106,132 , Ramstadius 106 , the Northern Hospital-Pressure Ulcer Prevention Plan (TNH-PUPP) 133 , Glamorgan Scale 134 , Conscious level, Mobility, Haemodynamics, Oxygen, Nutrition (COMHON) Index 135 , Reaper Oral Mucosa Pressure Injury Scale (ROMPIS) 136 , modified ROMPIS 137 , Braden Score 138,139 , and the interRAI scale 112 . Risk factors for developing PIs are shown in Table 6.…”
Section: Australian Studiesmentioning
confidence: 99%